Implementasi Nilai-Nilai Kearifan Lokal Dan Sejarah Pondok Pesantren Sa’adatudaren Pada Pembelajaran Sejarah - DWI FITRIANSYAH, RIVAN (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
Indonesia becomes one of the countries that has an island-shaped mainland, it is unique to this country, with an island shaped country and has many scattered territories as well as filled with a variety of religious and cultural patterns. And one of the regions that stands above the Indonesian pavilion is Jambi. The long history of the Sa’adatuddaren festival that is in Jambi is one evidence of the local wisdom that occurs in the middle of the community, especially the Arab villages. But now, in the midst of an era of destruction that can take away the local wisdom that already exists, there must be a way to overcome it. This article uses qualitative descriptive research methods with a library study approach with measures of collecting sources, performing analysis on sources, data collection, data reduction, data presentation, conclusion drawings and verification. And based on the study of the library that has been obtained, it can be concluded that the implementation of local wisdom values as a source of learning is the essence of the traditional learning of the Sa’adatudaren Pondok Pesantren. It is known that this training is the oldest training that has been undertaken by Jambi city which has been standing since 1915 suitable and relevant to be used as a teaching material on the subject of the history of combat because of this material there is also periodization which is relevant with the material “Thinking history (dichronic and synchronous)”. Using literature as well as the existence of the training house and the Arab village area in the opposite city.